Receivables and Payables in Operational Cash Flow: Case Study from a Hospital in Dumai City, Indonesia - Yanti, Meri; Anisha , Nurul; Fazira , Thasiya (Golden Ratio of Data in Summary, 2025)
Accounts receivable are corporate assets or a collection of company invoices from selling products or services using a deferred sales system for a predetermined period. Meanwhile, trade debt is a company's obligation from purchasing products or services in the past and must be paid immediately within a specific time frame. Furthermore, Operational Cash Flow is a report that provides cash inflows and outflows associated with a company's operations during a specific period and explains the sources of cash revenues and expenditures. The research intends to examine the impact of Accounts Receivable and Accounts Payable on Operational Cash Flow at XYZ Hospital. This study used a qualitative research method. This study analyzed what happens to Accounts Receivable and Payable on Operational Cash Flow. According to the findings of this study, Hospital XYZ's accounts payable and receivable management followed standard operating procedures (SOP). However, it has not been completely implemented regarding monitoring, and there are various roadblocks.